2001
DOI: 10.1046/j.1365-3164.2001.00214.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and histological evaluation of an analogue of palmitoylethanolamide, PLR 120 (comicronized Palmidrol INN) in cats with eosinophilic granuloma and eosinophilic plaque: a pilot study

Abstract: Fifteen cats with eosinophilic granuloma or eosinophilic plaque were given PLR 120 at the dosage of 10 mg kg-1 twice daily for one month. PLR-120 down-modulates mast cell degranulation via a receptor-mediated mechanism. No other drugs were permitted and cats were kept free of parasites throughout the study. A clinical evaluation and skin biopsies were performed before and after the treatment. Clinical improvement was assessed at 15 and 30 days. Mast cell numbers were counted and their granular content was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 53 publications
4
46
0
Order By: Relevance
“…As PEA is produced during inflammation (see Section 3.1 above), it was proposed that PEA acted as an "ALIAmide" (Autocoid Local Inflammation Antagonist Amide). A more recent study has demonstrated positive effects of PEA towards mast cell degranulation in 10 of 15 cats with eosinophilic granuloma or eosinophilic plaque [56]. Thus PEA may represent the basis of a new approach to the treatment of inflammation [57].…”
Section: Cannabinoid (Cb) Receptorsmentioning
confidence: 99%
“…As PEA is produced during inflammation (see Section 3.1 above), it was proposed that PEA acted as an "ALIAmide" (Autocoid Local Inflammation Antagonist Amide). A more recent study has demonstrated positive effects of PEA towards mast cell degranulation in 10 of 15 cats with eosinophilic granuloma or eosinophilic plaque [56]. Thus PEA may represent the basis of a new approach to the treatment of inflammation [57].…”
Section: Cannabinoid (Cb) Receptorsmentioning
confidence: 99%
“…Re et al (2007) concluded that the use of natural compounds such as PEA influences endogenous protective mechanisms and can represent an advantageous and beneficial novel therapeutic approach in veterinary medicine. Regarding dermatology, Scarampella et al (2001) administered the substance PLR 120 (an analogue of PEA) to 15 cats with eosinophilic granulomas or eosinophilic plaques. Clinical improvements of signs and lesions were evident in 10 out of 15 cats, suggesting that PLR-120 could be a useful drug for the treatment of these disorders (Scarampella et al 2001).…”
Section: The Use Of Cannabinoids In Animalsmentioning
confidence: 99%
“…Regarding dermatology, Scarampella et al (2001) administered the substance PLR 120 (an analogue of PEA) to 15 cats with eosinophilic granulomas or eosinophilic plaques. Clinical improvements of signs and lesions were evident in 10 out of 15 cats, suggesting that PLR-120 could be a useful drug for the treatment of these disorders (Scarampella et al 2001). Similarly, Cerrato et al (2010) isolated mast cells from the skin biopsies of 18 dogs, incubated these cells with IgE-rich serum and challenged them with anti-canine IgE.…”
Section: The Use Of Cannabinoids In Animalsmentioning
confidence: 99%
“…This AEA congener is produced on-demand within the lipid bilayer via N-acylphosphatidylethanolamine phospholipase D (NAPEPLD) [37], and its signal is quickly terminated through its degradation catalysed by at least two enzymes: the fatty acid amide hydrolase (FAAH) [38] and the ethanolaminehydrolyzing acid amidase (NAAA) [39]. Numerous evidence have shown that PEA can produce anti-inflammatory activity [40], analgesia in inflammatory and neuropathic pain [41,42], inhibition of food intake [43], reduction of gastrointestinal motility [44], inhibition of cancer cell proliferation [45], anti-pruritic effect [46], antiepileptic action [47], and neuroprotective activity through the activation of some kinases such as ERK1/2 MAP kinase and Akt proteins involved in the antioxidative mechanisms [48]. Neurobiological mechanisms underlying the effects produced by PEA are not yet fully understood, however, three synergistic mechanisms of action have been proposed.…”
Section: Palmitoylethanolamide Informationmentioning
confidence: 99%